SIKAP SOSIAL BUDAYA MASYARAKAT KALIMANTAN TIMUR TERHADAP KEHADIRAN IBU KOTA NEGARA BARU - Zein Syihabul Millah, Moch.; Agus Machfud Fauzi (Paradigma, 2025)
Abstract Developments regarding the relocation of the national capital through appropriate studies and studies from among existing perspectives, there is a positive potential to be found in the policy of moving the capital city, increasing equity in the economic sector which is not only focused on one regional development but in several other cities which are included in the territory of the Republic of Indonesia " The Unitary State of the Republic of Indonesia". Now in the capital city of Jakarta, the rate of development of growth centers is very high, far surpassing other large islands such as Sumatra, Kalimantan, Sulawesi and Papua. The relocation of the capital city as far as possible refers to economic connectivity as a trigger to increase the economy of other islands in Indonesia. With the transfer of IKN, it is hoped that socio-culture can be mixed and can support each other between cultures, which were originally in East Kalimantan with the arrival of immigrants from the city of Jakarta. that has been carried out by the government and the benefits of the research studied in this paper in order to have a broad insight into people’s behavior .The results in this study found the attitude of the people who accepted the existence of a new capital city to be built in East Kalimantan, both ethnicity and customs. because previously it didn’t have a bad track so acceptance was easy to happen. Keywords: Kalimantan; Society; State; Culture; City